Effect of Size of Giant Component for actor node selection in WSANs: A comparison study. (8th January 2019) - Elmazi, Donald; Cuka, Miralda; Ikeda, Makoto; Barolli, Leonard
Summary: Wireless Sensor and Actor Network (WSAN) is formed by the collaboration of micro‐sensor and actor nodes. Whenever there is any special event, ie, fire, earthquake, flood or enemy attack in the network, sensor nodes have responsibility to sense it and send information towards an actor node. The actor node is responsible to take prompt decision and react accordingly. In this work, we propose and implement two Fuzzy Based Systems (FBS): FBS1 and FBS2 for actor selection in WSANs. Different from FBS1, in FBS2, we added the Size of Giant Component (SGC) as new parameter. The systems decide whether the actor will be selected for the required job or not, based on data supplied by sensors and actual actor condition. We evaluated the proposed system by computer simulations. Comparing FBS1 with FBS2, we can see that SGC parameter that is used in FBS2 gives to the system a better performance due to the growth of SGC parameter.